2016
DOI: 10.1186/s12884-016-0951-7
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal near miss and mortality due to postpartum infection: a cross-sectional analysis from Rwanda

Abstract: BackgroundThe objective of this study is to evaluate ‘near miss’ and mortality in women with postpartum infections.MethodsWe performed a retrospective review of all patients referred to the University Teaching Hospital of Kigali (CHUK) between January 2012 and December 2013. We identified 117 patients with postpartum infections. Demographic data, length of admission, location of referral, initial surgery and subsequent treatment modalities including antibiotic administration and secondary surgery were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…This is the first prospective multicentre case control study combining maternal death and maternal near-miss in Rwandan district hospitals, where geographic access to emergency obstetric care is more of an issue than in Kigali capital city [ 9 , 10 ]. Based on an analysis of SMO that occurred in four district hospitals, this study assessed the quality of care provided, using the WHO criteria adapted to the local context [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first prospective multicentre case control study combining maternal death and maternal near-miss in Rwandan district hospitals, where geographic access to emergency obstetric care is more of an issue than in Kigali capital city [ 9 , 10 ]. Based on an analysis of SMO that occurred in four district hospitals, this study assessed the quality of care provided, using the WHO criteria adapted to the local context [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, cross-comparative findings reveal that private facilities offer significantly better outcomes in terms of CSD-related maternal mortality [59] and public health institutions show worse outcomes of severe morbimortality versus VD [43,58]. The comparison features show a similar trend while using the Robinson approach for perinatal mortality, neonatal distress, and maternal mortality ratio [44,46,50], or maternal CSD complications [49].…”
Section: Discussionmentioning
confidence: 93%
“…It is worth noting that Rwanda has a mechanism in place to conduct maternal death audits, and the country is currently in the process of institutionalizing ‘near-miss’ audits and confidential enquiries into maternal deaths [25]. Some studies recently reported rather high rates of postpartum haemorrhage and infection, as causes of maternal near miss and death [26,27]. This indicates a need for improvement of quality of care at the level of district hospitals, where the majority of deliveries occur.…”
Section: Discussionmentioning
confidence: 99%